026 Characteristics of advanced parkinson's disease patients seen in movement disorder clinics – australian results from the cross-sectional observe study. Issue 6 (24th May 2018) - Evans, Andrew; Fung, Victor SC; O'Sullivan, John; Stell, Rick; White, Richard; Williams, David; Onuk, Koray
Abstract : Introduction: To evaluate the proportion of Parkinson's disease (PD) patients identified as having advanced Parkinson's disease (APD) according to physician's judgement: Australian results. Methods: This cross-sectional, non-interventional observational study was performed in movement disorder clinics from 18 countries. Results from the Australian cohort are presented here. Participants included consecutive adults with PD attending a routine clinical visit, or inpatients at participating clinical sites, and who could speak English. The primary outcome was the proportion of patients diagnosed with APD via physician judgement. Secondary objectives included to evaluate clinical characteristics of APD versus non-APD; to assess the percentage of APD considered for device-aided therapies (DAT); to explore referral practices for APD; and to compare the percentage of APD identified in routine clinical practice by physician's judgment to APD identified based on APD criteria derived using the Delphi method. Results: 100 patients were recruited in Australia: 61.0% (95%CI 51.4%–70.6%) diagnosed with APD by physician judgement. Patients were 66.6±8.5 years, 65% were male, were living at home (97%), and diagnosed for median 10.7 years (0–30.5 years). Motor fluctuations were present in 68%. For those with APD, referral was predominantly to enable access to DAT (49%), while for non-APD, referral was largely for diagnostic purposes (41%). Referral to a movement disorder clinic occurred 4.8 years (median) following diagnosis for APD, or 3.6 years for non-APD. While 62% were eligible for DAT, only two-thirds of these received them. The most commonly used DAT was deep brain stimulation (64.3%). There was fair agreement between physician's judgement and the APD criteria by Delphi method (Cohen's kappa) 0.325 (95%CI 0.150–0.500). Conclusion: The definition of APD requires refinement in order to facilitate greater agreement among movement disorder specialists. A third of PD patients eligible for DAT remain untreated. Current Australian practice is weighted towards deep brain stimulation.